Changes in the mucosa of the Roux-limb after gastric bypass surgery - Spak, Emma; Björklund, Per; Helander, Herbert F.; Vieth, Michael; Olbers, Torsten; Casselbrant, Anna; Lönroth, Hans; Fändriks, Lars (Histopathology, 2010)
Spak E, Björklund P, Helander H F, Vieth M, Olbers T, Casselbrant A, Lönroth H & Fändriks L (2010) Histopathology-57, 680-689-Changes in the mucosa of the Roux-limb after gastric bypass surgeryAims:- Roux-en-Y gastric bypass surgery is the most efficient treatment of morbid obesity, but the mechanisms of action are still poorly understood. The aim of this study was to explore the Roux-limb mucosa after gastric bypass surgery, focusing upon basic morphology and inflammation.Methods and results:- Jejunal mucosal samples from the Roux-limb were gathered from eight patients at time of surgery and 6-8-months postsurgery. Histological evaluation of inflammation and morphometric investigations were performed, cell proliferation was assessed using immunohistochemistry and inflammatory markers and angiotensin (Ang) II receptors were detected using Western blot. Cell proliferation increased and villous surface area decreased in the Roux-limb mucosa but no signs of active inflammation were observed after surgery. Protein analyses showed increased levels of nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, myeloperoxidase (MPO) and the Ang II type 1(AT1) receptor after surgery, whereas the levels of inducible nitric oxide synthase (iNOS), nitrotyrosine and the Ang II type 2(AT2) receptor remained constant.Conclusion:- These results indicate that the phenotype of the jejunal mucosa changes once exposed to undigested food and the increased microbial load in the Roux-limb after surgery. © 2010 Blackwell Publishing Limited.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Angiotensin II receptors; Biochemical signs of inflammation; Mucosal adaptation; Obesity surgery; Villous surface area